Performance analysis of solar air heater duct roughened with multigap V-down ribs combined with staggered ribs. (June 2016) - Deo, Narinderpal Singh; Chander, Subhash; Saini, J.S.
Abstract: An experimental study has been conducted to investigate heat transfer, friction factor and thermo-hydraulic performance characteristics of flow in a rectangular duct artificially roughened on one side with multi-gap V-down ribs combined with staggered ribs. The rectangular duct used had aspect ratio of 12 and the Reynolds number based upon the mass flow rate of air at inlet of the duct ranged from 4000 to 12, 000. The rib pitch-to-height (P/e) ratio was varied from 4 to 14, rib height-to-hydraulic diameter (e/Dh ) ratio from 0.026 to 0.057 and angle of attack (α) from 40° to 80° while, gap width to rib height (g/e) ratio of 1, staggered rib length to rib height ratio (w/e) of 4.5, relative staggered rib pitch (p/P) value of 0.65 and two number of gap (n) on each side of the V-leg were used as fixed parameters during the experimentation. Results show two peaks for Nusselt number corresponding to the P/e value of 6 and 12 and decrease in the Nusselt number was observed for increase in the e/Dh value beyond 0.044. The maximum enhancement achieved in Nusselt number and thermohydraulic performance parameter was of 3.34 and 2.45 times respectively. Highlights: Two peaks in the Nusselt number versus relative roughness pitch graph. Better performance at higher relative roughness pitch (P/e = 12). Simple and economical design of the roughness elements. Not continuous increase in the Nusselt Number and friction factor with increase in e/Dh. Superior performance in comparison to other continuous and broken V-rib geometries.